Utilization of Rambutan Peel and Kelulut Honey in Herbal Lip Balm Production to Empower PKK Mothers - Raysharie, Puput Iswandyah; Kalalinggi, Septaria Yolan; Bancin, John Budiman; Rasidah, Rasidah; Ompusunggu, Dicky Perwira; Nafisah, Zahrotun (Universitas Lambung Mangkurat, 2025)
This community service program aimed to enhance the entrepreneurial skills and economic independence of the Bahu Palawa Village community by training members of the Family Welfare Movement (PKK) to produce herbal lip balm using rambutan peel waste and kelulut honey. The program adopted a Participatory Action Research (PAR) approach, actively involving participants in each stage: basic entrepreneurship training, dissemination of information on the benefits of local ingredients, hands-on lip balm production, digital marketing, and packaging design. The training combined expository instruction, demonstrations, and practical activities to ensure comprehension and application. Evaluation was conducted using pretest-posttest instruments and Wilcoxon signed-rank statistical analysis. Results showed a significant increase in participants’ understanding of rambutan peel benefits (from 12 to 28 participants) and of kelulut honey (from 22 to 29 participants), as well as improved trust in the safety of herbal cosmetics (from 31 to 32 participants). Satisfaction surveys indicated high approval of the training materials and mentoring. The program successfully increased knowledge, skills, and awareness of local resource potential. Its impact includes fostering interest in transforming organic waste into economically valuable products, although continued mentoring is needed to support sustainable independent production.